Pelatihan tentang Peningkatan Produksi ASI di PMB Latifah Nur - Tuhu Perwitasari; Suci Rahmani Nurita; Lulu Fahkrunisa; Nurbaiti Nurbaiti; Laida Sanilpa Tiwi (3031-8572, 2025)
Breast milk (ASI) is a fat emulsion in a solution of proteins, lactose, and organic salts secreted by the mother’s mammary glands as the primary food for infants. A common problem arises when breast milk production is not optimal, causing infants to receive an insufficient amount of milk, which may lead to frequent hunger and hinder their growth and development. Midwives play a crucial role in providing education to pregnant and breastfeeding mothers to prepare for the lactation period by increasing breast milk production. This community service activity was delivered to midwives at PMB Latifah Nur with the aim of enhancing their knowledge regarding improving breast milk production and preparing for the lactation period early—starting from family planning, during pregnancy, and throughout breastfeeding. As midwives, providing attention to infant growth and development by ensuring adequate breast milk intake is an essential responsibility supported through this community service program. The activity was conducted on February 22, 2025. The methods included health education, demonstrations of proper breastfeeding techniques, the use of local plants to support milk production, hands-on oxytocin massage practice, and an interactive question-and-answer session. Evaluation was carried out using pre-tests and post-tests to measure improvements in participants’ understanding. The results showed a significant increase in participants’ knowledge regarding factors affecting breast milk production, breast care techniques, and steps to stimulate oxytocin and prolactin hormones. Participants also reported improved confidence in applying lactation practices in daily life. This activity is expected to become a sustainable program to support successful breastfeeding and improve the health status of mothers and infants